Long-term risk of renal and urinary tract diseases in childhood cancer survivors: A population-based cohort study. (September 2016) - Bonnesen, Trine Gade; Winther, Jeanette F.; Asdahl, Peter H.; de Fine Licht, Sofie; Gudmundsdottir, Thorgerdur; Sällfors Holmqvist, Anna; Madanat-Harjuoja, Laura-Maria; Tryggvadottir, Laufey; Wesenberg, Finn; Birn, Henrik; Olsen, Jørgen H.; Hasle, Henrik; et al.
Abstract: Background: Childhood cancer has been associated with long-term risk of urinary tract diseases, but risk patterns remain to be comprehensively investigated. We analysed the lifetime risk of urinary tract diseases in survivors of childhood cancer in the Nordic countries. Methods: We identified 32, 519 one-year survivors of childhood cancer diagnosed since the 1940s and 1950s in the five Nordic cancer registries and selected 211, 156 population comparisons of a corresponding age, sex, and country of residence from the national population registries. To obtain information on all first-time hospitalizations for a urinary tract disease, we linked all study subjects to the national hospital registry of each country. Relative risks (RRs) and absolute excess risks (AERs) and associated 95% confidence intervals (CIs) for urinary tract diseases among cancer survivors were calculated with the appropriate morbidity rates among comparisons as reference. Results: We observed 1645 childhood cancer survivors ever hospitalized for urinary tract disease yielding an RR of 2.5 (95% CI 2.4–2.7) and an AER of 229 (95% CI 210–248) per 100, 000 person-years. The cumulative risk at age 60 was 22% in cancer survivors and 10% in comparisons. Infections of the urinary system and chronic kidney disease showed the highest excess risks, whereas survivors of neuroblastoma, hepatic and renal tumours experienced the highest RRs. Conclusion: Survivors of childhood cancer had an excess risk of urinary tract diseases and for most diseases the risk remained elevated throughout life. The highest risks occurred following therapy of childhood abdominal tumours. Highlights: Little is known about urinary tract late effects in childhood cancer survivors. We studied hospitalization of a large series of childhood cancer survivors. The risk was highest in survivors of leukaemia, neuroblastoma, and Wilms tumour. Chronic kidney disease and urolithiasis were among the most prevalent late effects. Urologists, nephrologists and late effects clinics should be aware of the lifelong increased risk of urinary tract diseases.